IMPLEMENTASI PROGRAM KELUARGA HARAPAN (PKH) DALAM UPAYA PENANGGULANGAN KEMISKINAN DI KECAMATAN HARAPAN DI KECAMATAN GAYAMSARI KOTA SEMARANG - Dela Putri Bestari, Kinanti; Santoso, R. Slamet; Subowo, Ari (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2024)
Poverty is a problem that occurs in every country, especially in developing countries like Indonesia. The government has taken various policies to solve the problem of poverty, one of which is through empowering poor families, namely the Family Hope Program (PKH). The Family Hope Program (PKH) is the development of a social protection system which aims to alleviate and help poor families with the hope that this program can reduce poverty. The method used is a qualitative-descriptive approach with data collection techniques through observation, interviews and documentation. The theory used in this research uses Merilee S Grindle's Policy Implementation Model theory which consists of two large dimensions, namely Policy Content and Implementation Environment. The results of the research show that the implementation of the family hope program has gone well but there are still several obstacles found, especially in terms of the degree of change desired regarding targeting within a year period regarding the number of KPM who must leave the transition period to graduate while resources are involved related to the availability of resources. human resources in the field and supporting facilities are still found to lack facilities for assistance in the field. This is also influenced by inhibiting factors such as lack of awareness among the community itself, there is a lack of human resources in dealing with beneficiary families, Facilitators of the Family Hope Program experience difficulties because the workload is not commensurate with the number of beneficiary families in Gayamsari District.